Efficacy and safety of dupilumab in a patient with metastatic clear cell renal cell carcinoma - César Ferreira; Egídio Freitas; Tiago Torres (Journal of International Medical Research)
This case report evaluated the efficacy and safety of dupilumab, a monoclonal antibody targeting interleukin-4 and interleukin-13, in a patient with atopic dermatitis (AD) and a history of metastatic renal cancer. Over 20 months of follow-up, the patient experienced significant improvement in AD symptoms without any recurrence of cancer. In addition to not stimulating carcinogenesis, dupilumab might synergistically inhibit tumor-induced immunosuppression, thereby potentially preventing tumor progression. This case suggests that dupilumab could be a viable treatment option for patients with AD and a history of solid neoplasms, filling a critical gap in current therapeutic approaches. Current evidence indicates that dupilumab does not promote cancer progression, but further research is necessary to confirm its long-term safety in this population. To establish robust scientific evidence and develop precise clinical guidelines, future studies should be randomized, controlled, and large-scale. This will help provide a definitive understanding of the safety and efficacy of dupilumab in patients with a history of cancer and inform clinical practice. In summary, although the initial findings are promising, comprehensive research is essential to ensure the optimal management of AD in patients with a history of malignancies.